1999
DOI: 10.1038/sj.ijo.0800971
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of measured and self-reported weight and height in a cross-sectional sample of young adolescents

Abstract: AIM: To explore the relationship between self-reported weight and height to actual weight and height in a crosssectional nationally representative sample of young adolescents. METHODS: Weights and heights were obtained on 1932 adolescents aged 12 ± 16 y enrolled in the NHANES III study. Self-reported weights and heights were available on 1657 of the adolescents (86%). RESULTS: Correlation between self-reported weight and actual weight ranged between 0.87 and 0.94, depending on gender or race. However, self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
322
3
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(364 citation statements)
references
References 12 publications
29
322
3
8
Order By: Relevance
“…Previous research has shown a high validity of self-reported BMI in older children and adolescents (Tienboon et al, 1992;Davis & Gergen, 1994;Strauss, 1999;Kuczmarski et al, 2000;Himes & Faricy, 2001). Prevalence of obesity in Greek children and adolescents D Karayiannis et al Goodman et al (2000) reported that 96% of adolescents correctly classified their obesity status based on self-reported data, and they concluded that self-reported height and weight could be used to accurately evaluate older children's and teens' obesity risk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown a high validity of self-reported BMI in older children and adolescents (Tienboon et al, 1992;Davis & Gergen, 1994;Strauss, 1999;Kuczmarski et al, 2000;Himes & Faricy, 2001). Prevalence of obesity in Greek children and adolescents D Karayiannis et al Goodman et al (2000) reported that 96% of adolescents correctly classified their obesity status based on self-reported data, and they concluded that self-reported height and weight could be used to accurately evaluate older children's and teens' obesity risk.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been demonstrated that adolescents aged 415 years tend to underestimate their weight and overestimate their height (Wang et al, 2002b;Brener et al, 2003). However, according to Strauss (1999), calculations of BMI are less inaccurate in children since they tend to underestimate both weight and height. As our OW prevalence compares favourably with other studies cited above conducted at a national scale on narrower age ranges and using measured weight and height (Rolland-Cachera et al, 2002;Labeyrie and Niel, 2003;Labeyrie and Niel, 2004), we believe that any underestimation would be insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Many studies have shown a high correlation between measured and selfreported height and weight, with height generally overestimated [5][6][7][8][9][10][11][12][13] and weight underestimated. [5][6][7][8]10,[12][13][14][15][16][17][18]23 Men, in particular, were more likely to overestimate their height, 10,12 and women were more likely to underestimate their weight. 5,7,11,13,17 It has been said that these biases in reporting might influence the distribution of BMI, and consequently the prevalence of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8]10,[12][13][14][15][16][17][18]23 Men, in particular, were more likely to overestimate their height, 10,12 and women were more likely to underestimate their weight. 5,7,11,13,17 It has been said that these biases in reporting might influence the distribution of BMI, and consequently the prevalence of obesity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation